Opinion in western Sweden 1995 - Bennulf, Martin (University of Gothenburg, 1996)
This survey forms part of the project 'Local environmental work - A study of local conditions and the interplay between economy and politics'. Other surveys used within this project are 'Local environment work 1995', 'SOM-survey 1995' and 'SOM-survey Western Sweden 1995'. Councillors in some thirty randomly chosen municipalities in Western Sweden had to answer a questionnaire dealing with environment, politics and media usage. The respondents had to state how often they read different types of papers, how much they read about different areas of politics and how often they watched/listened to news programs in TV or on the radio. Questions on politics and society dealt with participation in the 1994 general election, preferred political party on national level, general interest in politics and interest in different areas of politics. Furthermore the respondents were to place the political parties and themselves on a political left-right scale as well as on a green dimension scale. A number of questions considered the respondent's party: how long the party had been represented in the council; number of mandates; methods used to bring out information in the 1994 local election campaign; cooperation with other parties represented in the council; most important issues; and how decisions are made how to vote in the council. The respondents had to state how worrying they considered a number of things to be for the future, and how much confidence they had in the work done by a number of institutions, groups and persons. They also had to give their opinion on the local political parties' politics in three different areas, environment, economy, and totally, by placing them on a scale ranging from 'very bad politics' to 'very good politics'. Other questions dealt with the respondent's opinion on environmental issues: the importance of engagement of local authorities in different issues; the importance of a number of groups in the local environmental work; what the respondent is prepared to do to save the environment; how often different activities is done by the respondent; opinion on different propositions in the Swedish environmental debate; and how serious the respondent consider different threats against the environment to be. Questions about leisure habits and values dealt with activities during the last year, health risks for the Swedish people, and importance of a number of values. Background information includes age, sex, education, occupation, union membership, size of household, and income.

This survey forms part of the project 'Local environmental work - A study of local conditions and the interplay between economy and politics'. Other surveys used within this project are 'Local environment work 1995', 'SOM-survey 1995' and 'SOM-survey Western Sweden 1995'. Councillors in some thirty randomly chosen municipalities in Western Sweden had to answer a questionnaire dealing with environment, politics and media usage. The respondents had to state how often they read different types of papers, how much they read about different areas of politics and how often they watched/listened to news programs in TV or on the radio. Questions on politics and society dealt with participation in the 1994 general election, preferred political party on national level, general interest in politics and interest in different areas of politics. Furthermore the respondents were to place the political parties and themselves on a political left-right scale as well as on a green dimension scale. A number of questions considered the respondent's party: how long the party had been represented in the council; number of mandates; methods used to bring out information in the 1994 local election campaign; cooperation with other parties represented in the council; most important issues; and how decisions are made how to vote in the council. The respondents had to state how worrying they considered a number of things to be for the future, and how much confidence they had in the work done by a number of institutions, groups and persons. They also had to give their opinion on the local political parties' politics in three different areas, environment, economy, and totally, by placing them on a scale ranging from 'very bad politics' to 'very good politics'. Other questions dealt with the respondent's opinion on environmental issues: the importance of engagement of local authorities in different issues; the importance of a number of groups in the local environmental work; what the respondent is prepared to do to save the environment; how often different activities is done by the respondent; opinion on different propositions in the Swedish environmental debate; and how serious the respondent consider different threats against the environment to be. Questions about leisure habits and values dealt with activities during the last year, health risks for the Swedish people, and importance of a number of values. Background information includes age, sex, education, occupation, union membership, size of household, and income.
Västsvensk opinion 1995
Keywords: Environment and conservation; Miljö och naturvård; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap